Laser restructuring and photoluminescence of glass-clad GaSb/Si-core optical fibres - S. Song (Nature Portfolio, 2019)
Semiconductor-core optical fibres are of interest for their non-linear optical and electro-optical properties. Here, GaSb/Si composite-core optical fibres were fabricated and a CO2 laser was used to facilitate controlled GaSb segregation within the silicon. This has implications for embedding light sources in IR-transmitting fibers